1994
DOI: 10.1007/bf02245062
|View full text |Cite
|
Sign up to set email alerts
|

Verticalization of behavior elicited by dopaminergic mobilization is qualitatively different between C57BL/6J and DBA/2J mice

Abstract: Behavioral effects of dopaminergic stimulation were evaluated in C57BL/6J mice and compared to the effects occurring in DBA/2J mice, an inbred strain with reduced densities of striatal dopamine receptors. Effects of apomorphine (0.5-64 mg/kg) alone and in combination with cocaine (30 mg/kg) were assessed using a time-sampling technique that classified climbing and leaning in separate categories. Locomotion was also assessed in a separate experiment. Climbing occurred in DBA/2J mice only at doses of apomorphine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In addition to locomotor activity, other dopamine-dependent behavioral domains including vertical rearing, stereotypies and time spent in the center region of the OF chamber were assessed (Chandler et al, 1990; Tirelli and Witkin, 1994; Pogorelov et al, 2005). Neither line 6 nor Drd2 -EGFP mice exhibited significant differences in vertical rearing or time spent performing stereotypic movements, either basally or in response to acute cocaine (Figures 2A–D).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to locomotor activity, other dopamine-dependent behavioral domains including vertical rearing, stereotypies and time spent in the center region of the OF chamber were assessed (Chandler et al, 1990; Tirelli and Witkin, 1994; Pogorelov et al, 2005). Neither line 6 nor Drd2 -EGFP mice exhibited significant differences in vertical rearing or time spent performing stereotypic movements, either basally or in response to acute cocaine (Figures 2A–D).…”
Section: Resultsmentioning
confidence: 99%
“…Common view holds that B6 is a high-activity strain, whereas the D2 is an intermediate-activity strain (Cabib, 2002; Crawley et al, 1997). This view, however, seems to represent only a broad average over studies, with some that reported B6 to be significantly more active (e.g., Bolivar, Caldarone, Reilly, & Flaherty, 2000, for females; Elmer, Gorelick, Goldberg, & Rothman, 1996; Gorris & van Abeelen, 1981; Hatcher et al., 2001; Logue, Owen, Rasmussen, & Wehner, 1997), many that did not detect a significant difference in activity (e.g., Bolivar et al, 2000, for males; Cabib & Bonaventura, 1997; Jones, Reed, Radcliffe, & Erwein, 1993; Rocha et al, 1998; Tirelli & Witkin, 1994; Tolliver & Carney, 1995; Womer, Jones, & Erwin, 1994), and at least one (Rogers at al., 1999) that found D2 mice to have significantly higher activity. It should be noted that these studies used different arena sizes (longer dimension of 40–60 cm), arena shapes (square, rectangular, or circular), light conditions (fully illuminated to complete darkness), and tracking techniques (photocells, photobeam, and video).…”
mentioning
confidence: 99%
“…The C57BL/6J mouse and the P rat are currently used as models for addiction studies [61][62][63][64][65][66]. They also consistently test as more anxious in assays to measure depression and anxiety when compared to other rodent models [56].…”
Section: Introductionmentioning
confidence: 99%
“…The comorbidity of these conditions with the expression of TTM is similar to the presentation seen in humans, further supporting the potential applicability of these rodents as animal models of TTM. The C57BL/6J mouse and the P rat are currently used as models for addiction studies [61][62][63][64][65][66]. They also consistently test as more anxious in assays to measure depression and anxiety when compared to other rodent models [56].…”
Section: Introductionmentioning
confidence: 99%